108k views
5 votes
Solve for system of linear equations by substitution
y = 2x + 3
y = 3x + 5

User Hkatz
by
5.7k points

1 Answer

3 votes

Answer:

(- 2, - 1 )

Explanation:

Given the 2 equations

y = 2x + 3 → (1)

y = 3x + 5 → (2)

Substitute y = 3x + 5 into (1)

3x + 5 = 2x + 3 ( subtract 2x from both sides )

x + 5 = 3 ( subtract 5 from both sides )

x = - 2

Substitute x = - 2 into either of the 2 equations and evaluate for y

Substituting into (1)

y = 2(- 2) + 3 = - 4 + 3 = - 1

solution is (- 2, - 1 )

User Ivo Coumans
by
4.9k points